Sosialisasi Stop Bullying Dalam Memberikan Lingkungan Sekolah Aman Di SD Al Jihad - Intani Rifqa Annisa; Hayin Nurjanah (Journal of Cross Knowledge, 2024)
The Real Work Lecture Program (KKN) provides students with the opportunity to deal with social problems such as bullying in elementary schools (SD). Bullying is a serious problem that has a negative impact on victims, perpetrators and witnesses. This interferes with children's psychological, social, and academic growth. The aim of the anti-bullying outreach program in Mulyorejo Village is to teach elementary school children about what bullying is, how it happens, and how important it is to respect other people. Schools provide a good response in preventing cases of stopping bullying at school by supervising students at school. This program is expected to change students' attitudes and behavior through lectures, interactive games and simulations that are adapted to the children's ages, as well as the participation of teachers and parents. It is hoped that the results will serve as a model for similar programs in other elementary schools and build a safe and secure learning environment. Not only that, this program has a positive impact, namely providing good education to students about the importance of preventing bullying, especially in the school and classroom environment.